التعدد المصطلحاتي في اللّسانيات العربية الحديثة - سرداني,إسحاق; سحالية,عبد الحكيم (University of Eloued جامعة الوادي, 2024)
ملخص: تناقش هذه الدراسة إشكالية تعدد المصطلح في الدراسات اللسانية العربية الحديثة، وهذا من خلال دراسة نموذج مصطلحي يتمثل في مصطلح اللسانيات العرفانية وتمثلاته العربيّة وذلك بهدف الوقوف على الأهداف التالية: - وضع العالم العربي إزاء المصطلح. - معرفة واقع اللسانيّات وماهي عليه مصطلحاتها من اضطراب. - معرفة بعض الأسباب المؤدّية إلى هذا الوضع المصطلحي في الوطن العربي. - معرفة كيفية تعامل الباحث العربي مع الوافد من المصطلحات الأجنبية. - معرفة مدى فاعلية الهيئات الرسمية والمؤسسات المختصة في الحد من هذا الوضع المصطلحي في الوطن العربي. - المساهمة في تقديم بعض الحلول والمقترحات. منهج الدراسة: وقد اعتمدنا في هذا على المنهج الوصفي في سرد مقابلات لمصطلح اللسانيات العرفانية، وأهم المسوغات التي ساقها أصحابها لما اختاروه من مقابلات. Abstract: This study discusses the problem of the multiplicity of the term in modern Arabic linguistic studies, through the study of a terminological model represented in the term mystical linguistics and its Arabic representations in order to identify the following objectives: The situation of the Arab world vis-à-vis the term. Knowing the reality of linguistics and what its terminology is a disorder. Knowing some of the reasons leading to this terminological situation in the Arab world. Knowing how the Arab researcher deals with the expatriate from foreign terms. Knowing the effectiveness of official bodies and competent institutions in reducing this terminological situation in the Arab world. Contribute to the submission of some solutions and proposals. Study Methodology: We have relied on the descriptive approach in narrating interviews for the term mystical linguistics, and the most important justifications given by their owners for their chosen interviews.
اللّسانيات العرفانية أنموذجاً
Keywords: لسانيات; لسانيات عرفانية; Terminology; Polygamy; Linguistics; Mystical linguistics